2015
DOI: 10.1007/978-3-319-23374-1_9
|View full text |Cite
|
Sign up to set email alerts
|

Where Snow is a Landmark: Route Direction Elements in Alpine Contexts

Abstract: Abstract. Route directions research has mostly focused on urban space so far, highlighting human concepts of street networks based on a range of recurring elements such as route segments, decision points, landmarks and actions. We explored the way route directions reflect the features of space and activity in the context of mountaineering. Alpine route directions are only rarely segmented through decision points related to reorientation; instead, segmentation is based on changing topography. Segments are descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Analysis of topographic feature glossaries, for example, has unveiled how classes such as processes and human intentions reflect human environmental experiences and can inform queries for topographical data analysis and mapping [73]. Analysis of VGI route directions has showed which types of landmarks and decision points support navigation in mountain areas [18], while further research has suggested ways of integrating this information for rescue operations [70]. Content analysis can also be facilitated through corpus linguistics techniques such as frequency-based analysis, identification of synonyms, or analysis of co-occurrences, performed on text pre-processed with part-ofspeech tags and syntactic relations [37,60].…”
Section: Textual Data In Spatial Information Sciencementioning
confidence: 99%
“…Analysis of topographic feature glossaries, for example, has unveiled how classes such as processes and human intentions reflect human environmental experiences and can inform queries for topographical data analysis and mapping [73]. Analysis of VGI route directions has showed which types of landmarks and decision points support navigation in mountain areas [18], while further research has suggested ways of integrating this information for rescue operations [70]. Content analysis can also be facilitated through corpus linguistics techniques such as frequency-based analysis, identification of synonyms, or analysis of co-occurrences, performed on text pre-processed with part-ofspeech tags and syntactic relations [37,60].…”
Section: Textual Data In Spatial Information Sciencementioning
confidence: 99%
“…Different conditions allow for establishing relevant contrasts, and can be enhanced by collecting more than one type of linguistic data. Note that CODA, in principle, can also be used to analyze existing language data, such as corpus data (e.g., Danino, 2014;Egorova, Tenbrink, & Purves, 2015); in such a case, data collection means identifying a suitable data set that can be meaningfully analyzed in this way.…”
Section: Discovering Spatial and Temporal Concepts In English Discoursementioning
confidence: 99%
“…Mountaineering is characterized by a close interaction with space in the process of navigation; till now, little research has looked into the way people experience and describe this unique type of space (Egorova, Tenbrink & Purves, 2015). We examine the use of a linguistic structure that reflects a certain perspective on a spatial scene -fictive motion (henceforth FM).…”
Section: Introductionmentioning
confidence: 99%